Small RNAs in mycobacteria: an unfolding story - Haning, Katie; Cho, Seung Hee; Contreras, Lydia M. (Frontiers in Cellular and Infection Microbiology, 2014)
Mycobacteria represent a class of powerful pathogens, including those causing tuberculosis and leprosy, which continue to be worldwide health challenges. In the last twenty years, an abundance of non-coding, small RNAs (sRNAs) have been discovered in model bacteria and gained significant attention as regulators of cellular responses, including pathogenesis. Naturally, a search in mycobacteria followed, revealing over 200 sRNAs thus far. Characterization of these sRNAs is only beginning, but differential expression under environmental stresses suggests relevance to mycobacterial pathogenesis. This review provides a comprehensive overview of the current knowledge of sRNAs in mycobacteria, including historical perspective and techniques used for identification and characterization.